Unacceptable but Tolerated Behavior - Anne L. Jefferson (Educational Considerations, 2008)
The literature discusses bullying in terms of the misuse of a power situation over another individual repeatedly. Single, isolated incidences do not qualify as an act of bullying. Rather, bullying is the repetition of these acts combined with the desire on the part of the individual with the greater power base to cause physical, emotional, or social distress in another individual.
Keywords: administration; anti-bullying; behavior